Correlation between the Dynamics of Nanoconfined Water and the Local Chemical Environment in Calcium Silicate Hydrate Nanominerals. Issue 44 (28th June 2021) - Musumeci, Valentina; Goracci, Guido; Sanz Camacho, Paula; Dolado, Jorge S.; Aymonier, Cyril
Abstract: Invited for the cover of this issue is Cyril Aymonier and co‐workers at University of Bordeaux and University of the Basque Country. The image depicts the different distributions of water molecules in xonotlite and tobermorite nanominerals synthesised in supercritical water. Read the full text of the article at 10.1002/chem.202100098 . Abstract : " In this work, we have employed the innovative supercritical water‐based technology for synthesising high crystalline calcium silicate hydrate nanominerals, finely controlling the Si‐OH and Ca‐OH contents. A key result of this study relies on the observation, for the first time, of a transformation from an ordered "ice‐like" water distribution in the Si‐OH‐rich model nanocrystal to a disordered "liquid‐like" one in the Ca‐OH‐rich counterpart ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 11309 ff. (DOI: 10.1002/chem.202100098 ).